A Process for Utilizing Disposable Face Masks in Hot Mix Asphalt (HMA) Pavement Construction - Rahat, Md. Hasibul Hasan (East Carolina University, 2022)
The COVID-19 pandemic has caused a tremendous rise in plastic waste pollution globally. Pollution instigated by plastic has been one of the greatest threats to our world even before the Coronavirus outbreak. It is believed that plastic pollution has worsened due to the disposing of millions of personal protective equipment (PPE), such as surgical face masks. The use of plastic waste as a modifier has significantly lowered the temperature susceptibility of pavements, improved asphalt performance, and lowered construction costs, while the recycling of plastic waste has improved the environmental quality and preserved the non-renewable resources. To reduce pandemic-generated wastes and enhance the asphalt rutting resistance, disposable face mask is used as an as an efficient and non-costly modifier to hot mix asphalt (HMA) mixtures. The goal of the thesis is to bring an advancement to the field of transportation infrastructure by evaluating the performance of the flexible pavement using shredded face masks (SFM) as a modifier of HMA mixture and developing a cost estimating calculator to estimate the cost of asphalt pavement construction with mask. Modified HMA mixes with SFM content ranging from 0% to 1.5% were prepared and tested for rutting using Asphalt Pavement Analyzer (APA). It was found that by increasing the SFM content from 0% to 1.5%, the modified samples showed admirable resistance to permanent deformation as rutting depth values decreased from 3.0 mm to 0.93 mm. However, this study has resulted in the improvement of the rutting resistance of hot mix asphalt samples by using shredded face masks (SFM) as a modifier of HMA. Specific contributions include the evaluation of face masks in hot mix asphalt (HMA), and the development of a safe collection procedure for disposable face masks and a cost estimation calculator in Excel to estimate the cost of asphalt pavement construction based with and without face masks. Finally, this research opens a new avenue for the development of sustainable asphalt pavements by reducing pollution and energy consumption and increases knowledge in these areas. The findings of this study provide valuable insights into future efforts by industry and government agencies to develop sustainable approaches for the transportation, energy, and environmental industries. Furthermore, this research could provide a solution to reduce the plastic waste that is polluting the environment due to the COVID-19 pandemic and reveals the scope of a cost-benefit analysis of the process so that economists can assess the socioeconomic benefits of using face masks in pavement construction.
Keywords: Asphalt pavement rutting; Face masks; Cost estimating calculator; Waste collection; COVID-19; Plastics wastes; Sustainability; Recycling